THE EFFECT OF WORK ENGAGEMENT, AND LEADERSHIP ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - SARI, DITA ELANDA; Bakri Hasanuddin; Rossanty, N.P. Evvy (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
This study aims to determine the effect of work engagement and leadership on employee performance through organizational commitment as an intervening variable (study at SAMSAT Office Region I Palu). The type of research is correlational. The research sample was all employees in SAMSAT Office Region I Palu as many as 72 people. This research uses the Structural Equation Modeling (SEM) method, which is operated with SMARTPLS. The results of this study indicate that (1) Work engagement affects employee performance, (2) Leadership affects employee performance, (3) Work engagement affects organizational commitment, (4) Leadership has no effect on organizational commitment, (5) Organizational commitment affects employee performance, (6) Work engagement affects employee performance mediated by organizational commitment, (7) Leadership has no effect on employee performance mediated by organizational commitment at the SAMSAT office in region I Palu.